Young women’s leisure time physical activity determinants: a mixed methods approach - Fernandez-Lasa, Uxue; Eizagirre-Sagastibeltza, Olaia; Cayero, Ruth; Romaratezabala, Estibaliz; Martínez-Abajo, Judit; Usabiaga, Oidui (Frontiers in Psychology, 2024)
Introduction The aim of the study was to analyze the habits, motives and barriers related to Leisure Time Physical Activity (LTPA) among young women of Gipuzkoa, from a mixed approach. Methods A total of 526 women aged 18–29 (24.60 ± 3.30 years) responded to the Gipuzkoa Women’s Physical Activity Questionnaire (GWPAQ), seven of which were later interviewed. Results The main motives for LTPA were intrapersonal — related to health and enjoyment — and to interpersonal networks. However, the main barriers facing LTPA were mostly intrapersonal, such as lack of time, tiredness, and laziness. Contextual factors such as the availability of safe spaces, previous negative experiences, or negative self-perception of motor competence also emerged as conditioning factors in young women’s LTPA habits. Discussion This study may help to promote policies aimed at incentivizing LTPA for young women based on their needs and interests, by addressing the diversity of factors.